Current account and capital mobility hypothesis: evidence from the G-7 - Gaglianone, Wagner Piazza (2004)
This paper investigates an intertemporal optimization model in order to analyze the current account of the G-7 countries, measured as the present value of the future changes in net output. The study compares observed and forecasted series, generated by the model, using Campbell & Shiller’s (1987) methodology. In the estimation process, the countries are considered separately (with OLS technique) as well as jointly (SURE approach), to capture contemporaneous correlations of the shocks in net output. The paper also proposes a note on Granger causality and its implications to the optimal current account. The empirical results are sensitive to the technique adopted in the estimation process and suggest a rejection of the model in the G-7 countries, except for the USA and Japan, according to some papers presented in the literature.